Pharmacogenetics of angiotensin‐converting enzyme inhibitor‐induced angioedema. Issue 2 (8th January 2019) - Liau, Yusmiati; Chua, Ignatius; Kennedy, Martin A.; Maggo, Simran
Abstract: Angioedema is a rare adverse effect of the commonly used angiotensin‐converting enzyme inhibitors (ACEi) and is reported to occur with a prevalence of 0.1%‐0.7%. Although most ACEi‐induced angioedema (ACEi‐A) cases are mild, severe cases requiring intensive care and even resulting in death have been reported in the literature. The mechanisms underlying ACEi‐A are not yet fully understood, but bradykinin and/or substance P accumulation resulting from inhibition of ACE is believed to play a crucial role. ACEi‐A occurs at variable frequencies across different racial groups, suggesting a genetic association with the development of ACEi‐A. To date, one genome‐wide association study and several candidate gene studies have been published on the association of genetic variation with ACEi‐A. Genetic associations reported have been attributed to several distinct mechanisms: (a) genes coding for alternative enzymes responsible for the degradation of bradykinin and/or substance P in the diminution of ACE activity (b) ACE gene function, (c) bradykinin receptor genes, (d) genes implicated in immune and inflammation regulation and (e) genes in the fibrinolytic and coagulation pathway. Despite several plausible genetic associations, there are currently no genetic variants with sufficient effect to be clinically useful. The low incidence of ACEi‐A suggests that a combination of genomic approaches with the capability to detect potentially important variants might be required to shed light on the mechanism of this adverse reaction. Additionally, many non‐genetic risk factors associated with ACEi‐A suggest the potential contribution of epigenetic dysregulation.